If $x,y,z>0$ and $\sum_{cyc}^{} x^2 (1-x) \ge 0 $, I have to prove that:

$\sum_{cyc}^{} x^2 y^2 (1-xy) \ge 0 $

Then, if $\sum_{cyc}^{} x=3,$ then I have to prove

$\sqrt [8] \frac {\sum_{cyc}^{} x^3}{3} \le \frac {3}{\sum_{cyc}^{} xy}$

I tried to use Jensen's inequality, for $f(x)=x^2 (1-x),$ $g(x)=x^3$, $f_1(x,y)=x^2 y^2 (1-xy)$, $g_1(x,y)=\frac{1}{xy}$ without any success. I tried also C-S inequality but I was wondering if $1-x, 1-xy>0$. Any help? Thank you


Your second inequality.

We need to prove that $$\left(\frac{x+y+z}{3}\right)^{19}\geq\left(\frac{xy+xz+yz}{3}\right)^8\frac{x^3+y^3+z^3}{3}.$$ We'll prove a stronger inequality:

Let $x$, $y$ and $z$ be positives. Prove that $$\left(\frac{x+y+z}{3}\right)^{16}\geq\left(\frac{xy+xz+yz}{3}\right)^{6.5}\frac{x^3+y^3+z^3}{3}.$$ Indeed, let $x+y+z=3u$, $xy+xz+yz=3v^2$, where $v>0$ and $xyz=w^3$.

Thus, we need to prove that $$u^{16}\geq v^{13}(9u^3-9uv^2+w^3),$$ which says that it's enough to prove the last inequality for a maximal value of $w^3$,

which happens for equality case of two variables.

Since the last inequality is homogeneous, we can assume $y=z=1$ and we need to prove that $$\left(\frac{x+2}{3}\right)^{16}\geq\left(\frac{2x+1}{3}\right)^{6.5}\frac{x^3+2}{3}$$ or $f(x)\geq0,$ where $$f(x)=16\ln(x+2)-6.5\ln(2x+1)-\ln(x^3+2)-8.5\ln3.$$ Now, $$f'(x)=\frac{(x-1)(13x^3-12x^2-18x+20)}{(x+2)(2x+1)(x^3+2)},$$ which gives $x_{min}=1$ and we are done!

Your first inequality:

The condition gives $$1\geq\frac{x^3+y^3+z^3}{x^2+y^2+z^2}.$$ Thus, we need to prove that $$\sum_{cyc}x^2y^2\geq\sum_{cyc}x^3y^3,$$ for which it's enough to prove that $$\frac{(x^2y^2+x^2z^2+y^2z^2)(x^3+y^3+z^3)^2}{(x^2+y^2+z^2)^2}\geq x^3y^3+x^3z^3+y^3z^3$$ or $$\sum_{cyc}(x^8y^2+x^8z^2-x^7y^3-x^7z^3+x^6y^2z^2-x^4y^3z^3)\geq0,$$ which is true by Muirhead.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.